Worldwide diversity in mammalian life histories: environmental realms and evolutionary adaptations - Beccari, E; Capdevila Lanzaco, P; Salguero-Gómez, R; Pérez Carmona, C (Wiley, 2024)
Mammalian life history strategies can be characterized by a few axes of variation, conforming a space where species are positioned based on the life history strategies favoured in the environment they exploit. Yet, we still lack global descriptions of the diversity of realized mammalian life history and how this diversity is shaped by the environment. We used six life history traits to build a life history space covering worldwide mammalian adaptation, and we explored how environmental realms (land, air, water) influence mammalian life history strategies. We demonstrate that realms are tightly linked to distinct life history strategies. Aquatic and aerial species predominantly adhere to slower life history strategies, while terrestrial species exhibit faster life histories. Highly encephalized terrestrial species are a notable exception to these patterns. Further, we show that different mode of life may play a significant role in expanding the set of strategies exploitable in the terrestrial realm. Additionally, species transitioning between terrestrial and aquatic realms, such as seals, exhibit intermediate life history strategies. Our results provide compelling evidence of the link between environmental realms and the life history diversity of mammals, highlighting the importance of differences in mode of life to expand life history diversity.